1998
DOI: 10.1093/humrep/13.6.1567
|View full text |Cite
|
Sign up to set email alerts
|

Seminal megavesicles with adult polycystic kidney disease

Abstract: Adult polycystic kidney disease has been found in association with pathological dilatation of the seminal vesicles in six patients. These men appeared normal on clinical examination, but had azoospermia or severe oligozoospermia. They were investigated by scrotal exploration with vasography, renal and transrectal ultrasound scans (TRUS), and percutaneous puncture of the seminal vesicles in one case, before and after resection of the ejaculatory ducts. This revealed that the gross dilatation of the seminal vesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
2

Year Published

1999
1999
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 14 publications
0
27
0
2
Order By: Relevance
“…Vasography shows mega-vesicles, with no visible obstruction. Hendry et al [45] recently showed that dilated SV in hypofertile men with polycystic kidney disease was not due to cysts, but to SV atonia responsible for a functional obstacle on the ejaculatory ducts (Fig. 5d).…”
Section: Ejaculatory Duct Obstructionmentioning
confidence: 93%
“…Vasography shows mega-vesicles, with no visible obstruction. Hendry et al [45] recently showed that dilated SV in hypofertile men with polycystic kidney disease was not due to cysts, but to SV atonia responsible for a functional obstacle on the ejaculatory ducts (Fig. 5d).…”
Section: Ejaculatory Duct Obstructionmentioning
confidence: 93%
“…Most authors reporting an association with ADPKD describe bilateral seminal vesicle cysts, although it is not certain whether these are acquired or congenital. Marked distension of the seminal vesicles (i.e., megavesicles) is a separate entity, described previously in a small number of studies in ADPKD patients [5][6][7]13]. The majority of previous reports of seminal vesicle dilatation have been in patients presenting with hematospermia but no known ADPKD [14,15].…”
Section: Discussionmentioning
confidence: 83%
“…The reported prevalence of seminal vesicle cysts in patients with ADPKD varies widely, from 6% by computed tomography (CT) [3] to 21%-60% by transrectal ultrasound [1,4]. Seminal vesicle dilatation is rarely reported in patients with ADPKD but has been found during infertility evaluations [5][6][7]. Mean seminal vesicle diameter has been reported to be greater in ADPKD patients than normal subjects by CT criteria [8].…”
Section: Introductionmentioning
confidence: 99%
“…Hendry et al [ 28 ] described 6 patients with this fi nding and determined that the gross dilatation of the seminal vesicles seen on TRUS was not caused by obstruction but by atonicity. These ultrasonic appearances, when described previously, were incorrectly thought to be due to seminal vesicle cysts.…”
Section: Seminal Vesiclesmentioning
confidence: 91%